Perceived stigma, discrimination and psychological problems among patients with epilepsy - Malik, Najma Iqbal; Fatima, Rabia; Ullah, Irfan; Atta, Mohsin; Awan, Ashraf; Nashwan, Abdulqadir J.; Ahmed, Saeed (Frontiers in Psychiatry, 2022)
Objective: Present research aimed to examine the effect of perceived stigma and discrimination on the psychological problems, i.e., depression, anxiety, and quality of life of epilepsy patients. Study Design: A purposive sampling technique was used in this cross-sectional study. Materials and Methods: The sample consisted of 186patients with epilepsy. The Stigma Scale, Depression Anxiety Stress Scale, and Quality of life in Epilepsy-10 were used to measure the study variables. Results: Findings showed that both the perception of stigma and discrimination have a significant positive correlation with depression as well as anxiety. Stigma is a significant positive predictor of depression and anxiety at [F (1, 184) = 27.8, 15.92, p< .001, .001 respectively] and explains 12.7% and 7.5% variance that could be attributed to Stigma. Stigma is also a significant predictor of quality of life at [F (1, 184) = 16.10, p< .001] and explains the 7.5% variance that could be attributed to Stigma. Results also indicate that discrimination is a significant positive predictor of depression and anxiety at [F (1, 184) = 32.39, 19.91, p< .001] and explains 15 % and 9.8 % variance, respectively, that could be attributed to Stigma. However, stigma negatively predicts quality of life at [F (1, 184) = 20.34, p< .001] and explains 10 % variance. Non-significant differences were found in all the demographic variables (i.e., gender, socio-economic status, and disease duration), except the quality of life was significantly high among individuals with high Socio-economic status. Conclusions: Stigma is significantly higher in epileptic patients and has a detrimental effect on the patient's quality of life, recovery, and prognosis. Thus, there is undoubtedly needed to address psychological issues, most notably the stigma associated with illnesses. Psychologists, psychiatrists, other physicians, and caregivers of epileptic patients must pay close attention to the stigma in this patient population.